Drug repurposing in pharmaceutical industry and its impact on market access: market access implications - Murteira, Susana (J Mark Access Health Policy, 2014)
BACKGROUND: Drug repurposing is a group of development strategies employed in order to overcome some of the hurdles innate to drug research and development. Drug repurposing includes drug repositioning, reformulation and combination. OBJECTIVE: This study aimed to identify the determinants of successful market access outcome for drug repurposing in the United States of America (USA) and in Europe. METHODS: The case studies of repurposing strategies were identified through a systematic review of the literature. Price information and reimbursement conditions for all the case studies were collected mainly through access of public datasources. A list of attributes that could be associated with market access outcome (price level and reimbursement conditions) was developed, discussed, and validated by an external expert group. Detailed information for all attributes was researched and collected for each case study. Bivariate regression models were conducted to identify factors associated with price change for all repurposing cases. A similar analysis was performed for reformulation and repositioning cases, in the USA and in Europe, separately. A significance level of 5% was used for all analyses. RESULTS: A total of 144 repurposing case studies were included in the statistical analysis for evaluation of mean price change. Combination cases (the combination of two or more individual drug components) were excluded from the statistical analysis due to the low number of cases retrieved. The main attributes associated with a significant price increase for overall repurposing cases were ‘change in administration setting to hospital’ (374%, p<0.0001), ‘addressing unmet needs’ (69%, p<0.05), ‘reformulations belonging to Group 3’—that is, change in administration route (117%, p<0.001), and being a repurposed product with the ‘same brand name’ as the original product (65%, p<0.05). CONCLUSION: We found that the ability of the repurposed product to address unmet needs, a reformulation where the target product had a different administration route than the source product, and having a similar brand name for repurposed and original products, were variables that impacted a positive price change for repurposed drugs overall. Our research results also suggested that orphan designation could have a positive impact for repositioning in the USA, in particular. Although a change of administration from ambulatory to hospital setting seemed to be significantly correlated with a price increase for the target product, only one case was retrieved for this parameter; as such, it was not possible to infer a firm correlation between this parameter and a change in price.